2014
DOI: 10.1186/1471-2458-14-1275
|View full text |Cite
|
Sign up to set email alerts
|

Mass fatality preparedness among medical examiners/coroners in the United States: a cross-sectional study

Abstract: BackgroundIn the United States (US), Medical Examiners and Coroners (ME/Cs) have the legal authority for the management of mass fatality incidents (MFI). Yet, preparedness and operational capabilities in this sector remain largely unknown. The purpose of this study was twofold; first, to identify appropriate measures of preparedness, and second, to assess preparedness levels and factors significantly associated with preparedness.MethodsThree separate checklists were developed to measure different aspects of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
2
19
1
Order By: Relevance
“…These strategies are supported by study data and literature on the role of FBOs in general emergency preparedness and response efforts. 12 Similar to results from MFI infrastructure studies, [10][11][12] it was found that participation in drills was associated with operational capabilities as well as with resource sharing partnerships. Improved clarity of role function and enhanced integration of FBOs in the overall MFI mission can be achieved through coordinated drills and training with their partners in the private and public sectors.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These strategies are supported by study data and literature on the role of FBOs in general emergency preparedness and response efforts. 12 Similar to results from MFI infrastructure studies, [10][11][12] it was found that participation in drills was associated with operational capabilities as well as with resource sharing partnerships. Improved clarity of role function and enhanced integration of FBOs in the overall MFI mission can be achieved through coordinated drills and training with their partners in the private and public sectors.…”
Section: Discussionsupporting
confidence: 52%
“…Using a cut-off point of 70%, which was based on previous staff surge capacity modeling for other types of disaster events, 10 , 11 only 20% of respondents thought that 70% or more of their FBO staff would be able to respond to MFIs, with or without CBRNE. A larger proportion (45%) thought that 70% or more of the FBO’s would be willing to respond to MFIs, although that proportion decreased to 37% if CBRNE agents were involved.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from the present study echo several studies found in the recent literature using iPad technology. Past research regarding mathematics interventions with technology have been focused on task on behavior (Flower, 2014 ; Riley et al, 2014 ) and correctly completed math problems (Haydon et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Medical examiners, coroners, and cemetery managers have much more to do during a disaster than identifying and interring victims. Gershon et al () identify tasks such as body management and security, crisis communication, morgue operations, volunteer management, and victim release to funeral homes or other entities. Depending upon the need, Disaster Mortuary Operational Response Teams can be deployed through the federal government's National Response Framework to aid with deathcare and death management.…”
Section: Mass Casualty Events and Burial Practicesmentioning
confidence: 99%
“…Depending upon the need, Disaster Mortuary Operational Response Teams can be deployed through the federal government's National Response Framework to aid with deathcare and death management. Based on a survey of mortuary operators, Gershon et al () found that most staff would need additional training, capacity, and funding to properly handle mass fatality incidents; the COVID‐19 pandemic is highlighting those needs. Merrill et al () had similar results, with survey respondents indicating that biological contaminants (such as the COVID‐19 virus) complicate their disaster response abilities.…”
Section: Mass Casualty Events and Burial Practicesmentioning
confidence: 99%